The piezoelectric properties of 3R molybdenum disulfide flakes - Cai, Weifan (Nanyang Technological University, 2021)
Low-dimensional nanomaterials, such as Wurtzite structured materials (ZnO, GaN, etc.), and transitional metal dichalcogenides (MoS2, WSe2, etc.), have been widely studied for their unique physical properties which result from strong coupling effect among piezoelectric, semiconducting, and optical characteristics. In depth understanding of the physical properties could promote development of various novel functional devices, energy harvesters, etc. The piezoelectricity in 3R (3 Rhombohedral) MoS2 has been predicated by theoretical studies. To our best knowledge, no experimental observation has been reported so far. In this thesis, the piezoelectricity of 3R MoS2 flakes has been studied systematically. Two kinds of flexible 3R MoS2 based piezoelectric nanogenerator (PENG) have been fabricated. One is aligned 3R MoS2 device, in which the zigzag direction is aligned to the electrodes direction, and another is non-aligned 3R MoS2 device. The aligned 3R MoS2 PENG shows superb electrical and excellent power density values. The crystal orientation dependent piezoelectric polarization generation can be clearly observed by the fact that the piezoelectric polarization depends on whether the strain is applied along the zigzag or the armchair direction. Specifically, the high piezoelectric response from 3R MoS2 is firstly confirmed using Piezoresponse Force Microscopy (PFM) at room temperature. The out-of-plane piezoelectric coefficient d33 is measured around 0.7 to 1.5 pm/V for multilayer 3R MoS2. From lateral PFM measurement, we observe a strong piezoelectric response due to the coupling of in-plane and out-of-plane piezoelectricity. Subsequently, we find that the intrinsic thermal conductivity of 3R MoS2 flake is slightly changed under mechanical strains. A strong modulation of heat transport is observed on 3R MoS2 flake and its metal contact junctions under biased strains. This is the first experimental observation which shows that heat transport of low dimensional piezoelectric material can be modulated through a mechanical strain. In addition, a flexible α-In2Se3/3R MoS2 van der Waals (vdWs) p-n heterojunction is fabricated for photodetection from the visible to near infrared region. It exhibits an ultrahigh photoresponsivity of 2.9 ×103 A/W and a substantial specific detectivity of 6.2 × 1010 Jones under a compressive strain of -0.26%. The transport of photon generated carriers is clearly modulated by mechanical stimuli through the piezoelectric effect at the heterojunction interface.